2022
DOI: 10.1111/ced.15158
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitan sesquioleate: a rare contact allergen that is also an important indicator of allergic contact dermatitis from crossreacting compounds as well as for false‐positive fragrance allergy

Abstract: Summary Background Controversy exists about the addition of sorbitan sesquioleate (SSO) to the European baseline series for concomitant patch testing, particularly with fragrance mix (FM) I and Myroxylone pereirae (MP), which both contain SSO as an emulsifier. Aim To investigate SSO contact sensitization and concomitant positive patch test reactions to FM I or MP in Turkey. Methods This was a retrospective analysis of 840 patients consecutively patch tested with SSO 20% petrolatum between 1996 and 2020. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The SSO contact allergy prevalence from this study (0.48%) remained similar to previous studies 10,18,19 . The prevalence of contact allergy to SSO in Europe was from 0.2% to 1.5% and seemed to be higher in other continents 5 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The SSO contact allergy prevalence from this study (0.48%) remained similar to previous studies 10,18,19 . The prevalence of contact allergy to SSO in Europe was from 0.2% to 1.5% and seemed to be higher in other continents 5 .…”
Section: Discussionsupporting
confidence: 87%
“…The SSO contact allergy prevalence from this study (0.48%) remained similar to previous studies. 10,18,19 The prevalence of contact allergy to SSO in Europe was from 0.2% to 1.5% and seemed to be higher in other continents. 5 Our study found irritant reactions in only two patients suggesting that SSO could rarely cause skin irritation by patch testing.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of reactions was also found in this study, strengthening the assumption that the concentrations of the mixes and the individual fragrance preparations should be further investigated and reconsidered. SSO contact allergy prevalence in this study was 0.8%, which could affect the interpretation of patch test readings when some test preparations, as demonstrated in the results, that is, FM I and BOP, contain it as an emulsifier 44–47 …”
Section: Discussionmentioning
confidence: 72%
“…SSO contact allergy prevalence in this study was 0.8%, which could affect the interpretation of patch test readings when some test preparations, as demonstrated in the results, that is, FM I and BOP, contain it as an emulsifier. [44][45][46][47] Oakmoss and treemoss, with atranol and chloroatranol content at trace levels, were expected to elicit significantly fewer reactions in patients. 36 Interestingly, some patients reacted positively only to the test substances with trace levels of atranol and chloroatranol, in similar numbers to those who reacted positively to the test substances with the standard levels.…”
Section: Discussionmentioning
confidence: 99%